Piagam Madinah: Resolusi Konflik Perdamaian Di Indonesia - Wahyuningsih, Fitria (LoroNG: Media Pengkajian Sosial Budaya, 2015)
The Medina Charter is a written agreement between the Muslims and non Muslims based on the convention of the Medina. It is as the result of the Medina community that was a plural society in the part of religion, tribe, race and ideology. Therefore, the Medina Charter was applied by the Prophet Muhammad so as to unite the whole Medina community in fostering a unity, brotherhood and peace. Then, the values of the Medina Charter can be used as the considerations behind the conflict resolution that occurs in Indonesia such as the burning of mosques in Tolikara and Papua, the issues of Shiites in Sampang, the cases of the Huria Katolik Batak Protestan church in Bekasi and many others. The main reason is Indonesia can be categorized as a plural country that has similarities to the Medina. Piagam Madinah merupakan perjanjian tertulis antara kaum muslim dengan nonmuslim. Mengingat masyarakat Madinah adalah masyarakat yang plural baik secara agama, suku, rasa, dan motif. Sehingga piagam Madinah sebagai upaya Nabi Muhammad SAW untuk mengikat seluruh masyarakat Madinah dalam membina persatuan, persaudaraan dan perdamaian. Maka nilai-nilai dari piagam Madinah dapat diambil ibrahnya sebagai resolusi konflik yang terjadi di Indonesia seperti pembakaran Masjid di Tolikara, Papua, kasus Syi’ah di sampang, kasus gereja HKBP (Huria Katolik Batak Protestan) di Bekasi, dan sebagainya. Karena Indonesia juga termasuk negara yang plural yang memiliki kemiripan dengan Madinah